2015
DOI: 10.1590/s0102-67202015000200015
|View full text |Cite
|
Sign up to set email alerts
|

Oral transit time: a critical review of the literature

Abstract: IntroductionOral transit time is one of the parameters observed during the clinical assessment of the swallowing function. The importance of this parameter is due to its impact on the total duration of a meal, whose consequence can be an unfavorable nutritional prognostic.ObjectiveTo document scientific papers that measure oral transit time in healthy subjects.MethodThe review followed the steps proposed by the Cochrane Handbook. The search was done via the PubMed database through the use of descriptors relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 21 publications
2
12
0
4
Order By: Relevance
“…The interval between EMG and apnoea onset during thin-liquid swallows, therefore, could be approximated to the oral transit time (OTT) and between onset of apnoea and offset of swallow sound to pharyngeal transit time (PTT). The present study as well as the existing reports is in consensus that the OTT is volume dependent [47,48]. The position was found to affect OTT but not PTT during solid swallows [49] but this study found both position and volume to significantly influence the PTT.…”
Section: Discussionsupporting
confidence: 70%
“…The interval between EMG and apnoea onset during thin-liquid swallows, therefore, could be approximated to the oral transit time (OTT) and between onset of apnoea and offset of swallow sound to pharyngeal transit time (PTT). The present study as well as the existing reports is in consensus that the OTT is volume dependent [47,48]. The position was found to affect OTT but not PTT during solid swallows [49] but this study found both position and volume to significantly influence the PTT.…”
Section: Discussionsupporting
confidence: 70%
“…This statement about the study of OTT is based on many considerations, among them the definition of the beginning and of the end of the oral phase of swallowing, considering the voluntary component exclusively present in this phase of deglutition. The definition of OTT used in most studies was initially described in 1983 24 and complemented in 1995, by the same author. Since then, the literature has still shown controversies about the definition and initial markers for the measurement of OTT, depending on the author, the study population and the consistency and volume of food 27,28,29,30,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The alterations of certain parameters by HSCMRI should be related to alterations of numbers on videofluorography (VF) associated with deterioration of swallowing with physical changes. 6,[12][13][14][15][16][17][18] Specifically, the proposed 4 parameters are OTT, OOT, PR1, and the tissue immobility score on HSCMR. Certainly, these 4 parameters were significantly correlated with the 3 grades-normal, slightly worse, and worse-on the present study's questionnaire, as in earlier reports.…”
Section: Discussionmentioning
confidence: 99%